Unraveling hierarchical genetic structure in a marine metapopulation: A comparison of three high‐throughput genotyping approaches - D’Aloia, Cassidy C.; Andrés, Jose A.; Bogdanowicz, Steven M.; McCune, Amy R.; Harrison, Richard G.; Buston, Peter M. (Molecular ecology, 2020)
Marine metapopulations often exhibit subtle population structure that can be difficult to detect. Given recent advances in high‐throughput sequencing, an emerging question is whether various genotyping approaches, in concert with improved sampling designs, will substantially improve our understanding of genetic structure in the sea. To address this question, we explored hierarchical patterns of structure in the coral reef fish Elacatinus lori using a high‐resolution approach with respect to both genetic and geographic sampling. Previously, we identified three putative E. lori populations within Belize using traditional genetic markers and sparse geographic sampling: barrier reef and Turneffe Atoll; Glover's Atoll; and Lighthouse Atoll. Here, we systematically sampled individuals at ~10 km intervals throughout these reefs (1,129 individuals from 35 sites) and sequenced all individuals at three sets of markers: 2,418 SNPs; 89 microsatellites; and 57 nonrepetitive nuclear loci. At broad spatial scales, the markers were consistent with each other and with previous findings. At finer spatial scales, there was new evidence of genetic substructure, but our three marker sets differed slightly in their ability to detect these patterns. Specifically, we found subtle structure between the barrier reef and Turneffe Atoll, with SNPs resolving this pattern most effectively. We also documented isolation by distance within the barrier reef. Sensitivity analyses revealed that the number of loci (and alleles) had a strong effect on the detection of structure for all three marker sets, particularly at small spatial scales. Taken together, these results illustrate empirically that high‐throughput genotyping data can elucidate subtle genetic structure at previously‐undetected scales in a dispersive marine fish. see also the Perspective by Laura E. Timm.